Hamiltonian analysis of exact integrability of the quantum 3-level superradiance Dicke model - Samuliak, R.V. (Український математичний журнал, 1992)
It is proved that the quantum 3-level superradiance Dicke model is exactly integrable. The Lax representation of the operator system of evolution equations is derived on the basis of a theory of Lie algebras of currents. The method employed in discussions of the quantum inverse scattering problem is applied to obtain quantum analogs of the action-angle variables. The spectra of the energy operator and of other quantum motion integrals as well as the exact one- and multiparticle excitation eigenstates of the model are constructed. It is shown that the model possesses states of constrained quasiparticles (quantum solitons) that induce superradiance pulses. Доведена точна інтегровність трирівневої квантової моделі надвипромінювання Дікке. На основі теорії алгебр Лі струмів побудовано зображення Лакса операторної системи еволюційних рівнянь. Методом оберненої квантової задачі розсіювання знайдено квантовий аналог змінних дія-кут. Побудовано спектри інтегралів руху та точні одно- і багаточастинкові збуджені стани моделі. Показано, що моделі притаманні стани зв’язаних квазічастинок (квантові солітонн), що спричиняють імпульси надвипромінювання.